Current state and potential of additive – hybrid manufacturing for metal parts. Issue 3 (18th April 2017) - Strong, Danielle; Sirichakwal, Issariya; Manogharan, Guha P.; Wakefield, Thomas
Abstract : Purpose: This paper aims to investigate the extent to which traditional manufacturers are equipped and interested in participating in a hybrid manufacturing system which integrates traditional processes such as machining and grinding with additive manufacturing (AM) processes. Design/methodology/approach: A survey was conducted among traditional metal manufacturers to collect data and evaluate the ability of these manufacturers to provide hybrid – AM post-processing services in addition to their standard product offering (e.g. mass production). Findings: The original equipment manufacturers (OEMs) surveyed have machine availability and an interest in adopting hybrid manufacturing to additionally offer post-processing services. Low volume parts which would be suitable for hybrid manufacturing are generally more profitable. Access to metal AM, process engineering time, tooling requirements and the need for quality control tools were equally identified as the major challenges for OEM participation in this evolving supply chain. Practical implications: OEMs can use this research to determine if hybrid manufacturing is a possible fit for their industry using existing machine tools. Originality/value: Survey data offer an unique insight into the readiness of metal manufacturers who play an integral role in the evolving hybrid supply chain ecosystem required for post-processing of AM metal parts. This study also suggests that establishing metal AM centers around OEMs as a shared resource to produce near-net AM parts would be beneficial.